2021
DOI: 10.48550/arxiv.2102.13298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Many-Qudit representation for the Travelling Salesman Problem Optimisation

Vladimir Vargas-Calderón,
Nicolas Parra-A.,
Herbert Vinck-Posada
et al.

Abstract: We present a map from the travelling salesman problem (TSP), a prototypical NP-complete combinatorial optimisation task, to the ground state associated with a system of many-qudits. Conventionally, the TSP is cast into a quadratic unconstrained binary optimisation (QUBO) problem, that can be solved on an Ising machine. The size of the corresponding physical system's Hilbert space is 2 N 2, where N is the number of cities considered in the TSP. Our proposal provides a manyqudit system with a Hilbert space of di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Much work has been done on qubit based hardware since it is what is most widely available, however recent studies have shown that qudit (d-state quantum objects) based algorithms are frequently more efficient for quantum computing [50,[79][80][81][82][83][84][85][86][87]. In addition there have been recent proof of principle implementations of qutrits [88][89][90][91][92][93][94][95] and cavity QED for qubit-qudit couplings [96][97][98][99][100][101][102].…”
Section: Introductionmentioning
confidence: 99%
“…Much work has been done on qubit based hardware since it is what is most widely available, however recent studies have shown that qudit (d-state quantum objects) based algorithms are frequently more efficient for quantum computing [50,[79][80][81][82][83][84][85][86][87]. In addition there have been recent proof of principle implementations of qutrits [88][89][90][91][92][93][94][95] and cavity QED for qubit-qudit couplings [96][97][98][99][100][101][102].…”
Section: Introductionmentioning
confidence: 99%